Amoebic liver abscess: a report from central India. (January 2016) - Chaudhary, Satyarth; Noor, Mohd. Talha; Jain, Sunil; Kumar, Ravindra; Thakur, Bhagwan Singh
Amoebic liver abscess is a serious but curable hepatic illness predominantly seen in tropical countries. We describe our experience of clinical presentation, laboratory parameters, radiological findings and treatment strategies. This is a retrospective analysis of 114 patients who were admitted from January 2012 to September 2014 at our centre. The mean age of presentation was 41.7 ± 13.9 years, the majority of patients were male (86.8%) with chronic alcoholism (63.2%). Most of the patients had a solitary right lobe liver abscess. Abdominal pain, fever, tachycardia and hepatomegaly were the most common clinical findings while hypoalbuminaemia, anaemia, leucocytosis and electrolyte imbalance were the most common laboratory abnormalities. A significant number of patients could be managed with antibiotics only (45.6%), percutaneous radiological drainage techniques being an important adjunct in selected cases (percutaneous needle aspiration, 20.2%; percutaneous pigtail catheter drainage, 30.7%). Surgical intervention was required in only a few cases (3.5%). Mortality was 3.5%.